(M-1)(2m-5)=0

Simple and best practice solution for (M-1)(2m-5)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (M-1)(2m-5)=0 equation:


Simplifying
(M + -1)(2m + -5) = 0

Reorder the terms:
(-1 + M)(2m + -5) = 0

Reorder the terms:
(-1 + M)(-5 + 2m) = 0

Multiply (-1 + M) * (-5 + 2m)
(-1(-5 + 2m) + M(-5 + 2m)) = 0
((-5 * -1 + 2m * -1) + M(-5 + 2m)) = 0
((5 + -2m) + M(-5 + 2m)) = 0
(5 + -2m + (-5 * M + 2m * M)) = 0
(5 + -2m + (-5M + 2mM)) = 0

Reorder the terms:
(5 + -5M + -2m + 2mM) = 0
(5 + -5M + -2m + 2mM) = 0

Solving
5 + -5M + -2m + 2mM = 0

Solving for variable 'M'.

Move all terms containing M to the left, all other terms to the right.

Add '-5' to each side of the equation.
5 + -5M + -2m + -5 + 2mM = 0 + -5

Reorder the terms:
5 + -5 + -5M + -2m + 2mM = 0 + -5

Combine like terms: 5 + -5 = 0
0 + -5M + -2m + 2mM = 0 + -5
-5M + -2m + 2mM = 0 + -5

Combine like terms: 0 + -5 = -5
-5M + -2m + 2mM = -5

Add '2m' to each side of the equation.
-5M + -2m + 2m + 2mM = -5 + 2m

Combine like terms: -2m + 2m = 0
-5M + 0 + 2mM = -5 + 2m
-5M + 2mM = -5 + 2m

Reorder the terms:
5 + -5M + -2m + 2mM = -5 + 2m + 5 + -2m

Reorder the terms:
5 + -5M + -2m + 2mM = -5 + 5 + 2m + -2m

Combine like terms: -5 + 5 = 0
5 + -5M + -2m + 2mM = 0 + 2m + -2m
5 + -5M + -2m + 2mM = 2m + -2m

Combine like terms: 2m + -2m = 0
5 + -5M + -2m + 2mM = 0

The solution to this equation could not be determined.

See similar equations:

| (6r-7s+8t)-(2r-3s+4t)= | | -7.70=10.8-7.4t | | 24+3n=24+1.5 | | 2x^3-7x^2-8x+28=0factoring | | 5d^2+9d-18=0 | | 7.9a+3.25=-14.13 | | 6x-1+7x=90 | | 7.9a+3.25=-14.1 | | 2x-9y=8 | | 4y=-6x-2 | | X^2-4ix-13=0 | | 6(d+6)-8=2*d+30 | | -51.98=7.7x+5 | | X^2+12=-18 | | (1/2)c=5 | | -1/6z=-4.5 | | 50+90t-4.9t^2=250 | | 3/4-6/8= | | 5.7+1.2n=3.06 | | 8.3y-9.8=13.44 | | 22.1/0.5= | | 3d^2-8d-11=0 | | 6/11p=-12/11 | | (x^3+8)(x^2+5x)=0 | | x^2+48x-1024=0 | | x+26.7=7.1 | | 27+s=23 | | 3x^2-2n-8= | | 3m^2+2m-1=0 | | x-11=-2x-5 | | -(18+15)=-18+(-15) | | 1.5x-12=3x/4 |

Equations solver categories